Aircraft engines and gas turbines - Kerrebrock, Jack L. (MIT, 1977)
Introduction to concepts - Ideal cycle analysis: trends - Cycle analysis with losses - Nonrotating components - Compressors and fans - Turbines - Engine structures - Component matching and engine performance - Aircraft engine noise - Hypersonic engines - Propulsion systems analysis.